2019
DOI: 10.15446/cuad.econ.v38n78.73540
|View full text |Cite
|
Sign up to set email alerts
|

Las Farianas: Reintegration of former female FARC fighters as a driver for peace in Colombia

Abstract: The 2016 peace agreement includes comprehensive prescriptions for the so-called “reincorporation” of former combatants into the social, economic and political life of Colombia. However, the literature is somewhat skeptical regarding the reintegration of female fighters, since they are usually either neglected or are facing intense stigmatization by the society. Nevertheless, based on empirical data from field research in 2018, we argue that both former FARC ex-combatants and conflict-affected communities large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 43 publications
0
3
0
3
Order By: Relevance
“…Previous research confirmed that reproduction was strictly regulated during wartimes (Anctil & Tillman, 2015; Bouvier, 2016). Motherhood was a denied capability, but not completely absent, due to the mobile nature of the guerrilla where most slept in tents, and the intense armed confrontations (Barrios & Richter, 2019; Barrios Sabogal, 2020). In the reports of the Centro Nacional de Memoria Histórica (2017, 2018) many women said they were forced to have abortions and, some had to leave their children with relatives or in the closest village to their area of operations.…”
Section: Results: Womens’ Struggles In a Post-peace Agreement Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research confirmed that reproduction was strictly regulated during wartimes (Anctil & Tillman, 2015; Bouvier, 2016). Motherhood was a denied capability, but not completely absent, due to the mobile nature of the guerrilla where most slept in tents, and the intense armed confrontations (Barrios & Richter, 2019; Barrios Sabogal, 2020). In the reports of the Centro Nacional de Memoria Histórica (2017, 2018) many women said they were forced to have abortions and, some had to leave their children with relatives or in the closest village to their area of operations.…”
Section: Results: Womens’ Struggles In a Post-peace Agreement Settingmentioning
confidence: 99%
“…Previous research has described new social roles of women's FARC-EP (Barrios & Richter, 2019; Barrios Sabogal, 2020), but there have been no gender analyses in terms of human development. Additionally, once they move from Territorial Spaces for Training and Reincorporation (ETCR) and are dispersed in many locations, it is harder to collect data.…”
Section: Introductionmentioning
confidence: 99%
“…En particular, se identifica la identidad fariana como un elemento clave en la construcción de comunidad. Es importante destacar también que estos procesos se dan en uno de los espacios territoriales para la reincorporación, lo cual puede facilitar el sentido de comunidad y el desarrollo de procesos colectivos (Barrios y Solveig, 2019). Estudios previos sobre el proceso de reincorporación han visibilizado las dificultades para consolidar el proyecto comunitario en los Espacios Territoriales de Capacitación y Reincorporación (ETCRs) debido a la falta de presencia estatal (Baquero-Melo, 2022).…”
Section: Discussionunclassified
“…Por ejemplo, podríamos comparar el concepto de colaboradora de Viterna con el de milicianas (urbanas o rurales) de las FARC-EP: no estaban necesariamente en armas, pero participaban clandestinamente en las células del Partido Comunista clandestino colombiano (PC3), en el Movimiento Bolivariano por la Nueva Colombia (MBNC) o, algunas, en los movimientos estudiantiles más ampliamente. 9 Los contextos de El Salvador y Colombia también implican diferencias en esta tipología. Por ejemplo, algunos espacios de politización difieren: los campamentos de refugiados son centrales para la militancia en el FMLN, mientras en las FARC-EP las organizaciones campesinas tuvieron un papel destacado desde el principio (Villamizar 2017).…”
Section: Militancia Política Poslucha Armada De Las Mujeresunclassified